1988
DOI: 10.1227/00006123-198806010-00024
|View full text |Cite
|
Sign up to set email alerts
|

Anaplastic Astrocytomas Associated with Previous Radiotherapy: Report of Three Cases

Abstract: In a group of 132 patients with malignant astrocytomas treated between 1971 and 1983, there were 3 patients who had received radiotherapy to the head several years before developing the glioma. The cases are described, and the evidence supporting the view that the gliomas might be radiation-induced is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
3

Year Published

1989
1989
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 0 publications
0
8
0
3
Order By: Relevance
“…That radiation may be implicated as a cause of human CNS gliomas is demonstrated by those patients who developed gliomas in the field of radiation at a rate higher than expected after receiving radiothera py for relatively benign conditions such as tinea capitis and pituitary tumors [11,14,[24][25][26][27][28][29][30][31][32][33][34][35][36]. Most radiationinduced intracranial gliomas have occurred following more than 3,000 rad [37-44], Criteria for defining a hu man neoplasm as radiation-induced are a long quiescent latent period, a location within the irradiated area and a tumor distinctly different from the lesion for which the patient was irradiated [11,29,34].…”
Section: Effects Of Cns Prophylaxismentioning
confidence: 99%
“…That radiation may be implicated as a cause of human CNS gliomas is demonstrated by those patients who developed gliomas in the field of radiation at a rate higher than expected after receiving radiothera py for relatively benign conditions such as tinea capitis and pituitary tumors [11,14,[24][25][26][27][28][29][30][31][32][33][34][35][36]. Most radiationinduced intracranial gliomas have occurred following more than 3,000 rad [37-44], Criteria for defining a hu man neoplasm as radiation-induced are a long quiescent latent period, a location within the irradiated area and a tumor distinctly different from the lesion for which the patient was irradiated [11,29,34].…”
Section: Effects Of Cns Prophylaxismentioning
confidence: 99%
“…7,11) Malignant transformation was confirmed within 3 years in two cases. 3) The patient backgrounds and therapeutic strategies differed in each case, but four of six patients (excluding six unknown cases) survived for less than 36 months. 3,7) The course of radiation-induced astrocytoma tends to be dismal, even with an initial histological diagnosis of astrocytoma.…”
Section: Discussionmentioning
confidence: 98%
“…Twelve cases of radiation-induced grade II astrocytoma are summarized in Table 1. [1][2][3]5,7,[10][11][12][13] The mean age was 25.7 years, and the male/female ratio was 7:5. The reason for first irradiation included acute lymphocytic leukemia (n = 5), tinea capitis (n = 3), germ cell tumor (n = 1), medulloblastoma (n = 1), meningioma (n = 1), and chronic ear infection (n = 1).…”
Section: Discussionmentioning
confidence: 99%
“…The three intracerebral secondary tumours have developed after RT for intracranial tumours, and all were situated at the edge of the irradiated volume. It has been found that patients with radiation-induced gliomas are often clearly younger than other patients who spontaneously develop gliomas [50]. In a review of 30 reports on gliomas after RT for pituitary adenoma or CP, Simmons and Laws [28] found young age, high histological grade and occurrence within the temporal lobe as typical features for the secondary tumours.…”
Section: Discussionmentioning
confidence: 99%